2016
DOI: 10.1542/peds.2015-3936
|View full text |Cite
|
Sign up to set email alerts
|

Asymptomatic Kawasaki Disease in a 3-Month-Old Infant

Abstract: Kawasaki disease (KD) is the leading cause of acquired heart disease in children in the United States. It is a systemic vasculitis characterized by diffuse inflammation of medium and small blood vessels. If untreated it can lead to myocardial infarction, ischemic heart disease, or sudden death. Early recognition and treatment decrease the incidence of coronary consequences, resulting in improved clinical outcomes. Incomplete KD is much less likely to fulfill major clinical diagnostic criteria. Infants <… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
8
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 13 publications
1
8
1
Order By: Relevance
“…3 However, Kawasaki disease without fever is well reported. [11][12][13][14] In contrast to our patient, these afebrile cases occurred in younger infants (younger than 13 months). Additionally, there have been reports of coronary sequelae and biomarkers consistent with Kawasaki disease, without the patient meeting the AHA criteria.…”
Section: Discussioncontrasting
confidence: 89%
“…3 However, Kawasaki disease without fever is well reported. [11][12][13][14] In contrast to our patient, these afebrile cases occurred in younger infants (younger than 13 months). Additionally, there have been reports of coronary sequelae and biomarkers consistent with Kawasaki disease, without the patient meeting the AHA criteria.…”
Section: Discussioncontrasting
confidence: 89%
“…Most (79%) of the patients had no principal clinical features at the onset of fever, while five patients (21%) had no features other than fever until the 5th day of illness. Our results indicate that it is difficult to diagnose incomplete KD in young infants younger than 3 months of age, because of presentation with unfulfilled criteria …”
Section: Discussionmentioning
confidence: 74%
“…In some cases, KD has been suspected in young infants without fever . Our study revealed that sterile pyuria, cerebrospinal fluid pleocytosis, and seizures associated with KD could potentially lead to misdiagnosis and treatment delay .…”
Section: Discussionmentioning
confidence: 81%
“…3) The clinical importance is further buttressed by the fact that coronary artery dilation can develop even in a patient with iKD presenting with no principal symptoms. 11) Although the national KD database in Japan revealed that coronary artery aneurysm occurred in 25% of iKD cases satisfying only one of the six principal symptoms, 4) to the best of our knowledge, detailed reports 12,13) of such cases are limited. In contrast to those case reports, 12,13) our report provided echocardiographic and angiographic evidence of the coronary artery aneurysms.…”
Section: Discussionmentioning
confidence: 99%